2012
DOI: 10.1007/s00436-012-2835-8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and distribution of Alaria alata, a potential zoonotic parasite, in foxes in Ireland

Abstract: The digenean trematode Alaria alata, an intestinal parasite of wild canids is widely distributed in Europe. The recent finding of the mesocercarial life cycle stage in the paratenic wild boar host suggests that it may potentially infect humans Mohl et al. (Parasitol Res 105:1-15, 2009). Over 500 foxes were examined during a wildlife survey for zoonotic diseases in 2009 and 2010. The prevalence of A. alata ranged from 21% to 26% in 2009 and 2010, and the intensity of infection varied, with the majority of foxes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
(45 reference statements)
2
22
0
1
Order By: Relevance
“…Infected boars in France have all been reported in lowlands (Portier et al, 2011). Our study shows that A. alata is very scarce above 200 m and another study focusing on foxes reported a 300 m elevation limit (Murphy et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Infected boars in France have all been reported in lowlands (Portier et al, 2011). Our study shows that A. alata is very scarce above 200 m and another study focusing on foxes reported a 300 m elevation limit (Murphy et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
“…These ecological needs lead to believe that A. alata cannot be found in areas with no convenient wetlands for both of these hosts (Murphy et al, 2012). The cluster analysis conducted in this study shows a cluster around the Rhine valley.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding mean intensity (3.3), Schöffel et al (1991) and Murphy et al (2012) also noted that the majority of infected foxes had a small parasitic burden. Several authors (Loos-Frank & Zeyhle 1982;Criado-Fornelio et al 2000;Eira et al 2006;Murphy et al 2012) confirm that the prevalence of A. alata is higher in territories rich in wet habitats. The complex life cycle of A. alata requires a freshwater snail as the first intermediate host and an amphibian as the second one.…”
Section: Resultsmentioning
confidence: 97%
“…larvae by a method consisting of an artificial digestion of a suitable sample of muscular tissue (European Commission 2005). In the course of this systematic inspection, numerous accidental discoveries of DMS in wild boars were made during the last 10 years in Germany, Croatia, France, Hungary, Ireland, Austria, and the Czech Republic (Jakšic et al 2002;Mileševic et al 2004;Große and Wüste 2006;Portier et al 2011;Murphy et al 2012;Széll et al 2013;Paulsen et al 2012Paulsen et al , 2013. The increasing number of these findings raised the concern about the public health risk posed by this parasite, in particular with regard to the consumption of insufficiently heated game meat, such as quick fries and short-ripened fermented sausages (BfR 2007;González-Fuentes et al 2014a).…”
Section: Introductionmentioning
confidence: 98%
“…Many mammalian, avian, and reptile species, among them wild boars (Dollfus and Chabaud 1953), can serve as paratenic hosts. Moreover, it is important to point out that the paratenic hosts can also infect each other, which leads to a notable expansion of the infection cycle (Möhl et al 2009;Murphy et al 2012). DMS-infected pigs were observed since the late nineteenth century (Duncker 1896).…”
Section: Introductionmentioning
confidence: 99%